AN ANALYSIS OF TEACHERS' QUESTIONING STRATEGIES IN EFL CLASSROOM AT SMP MULIA PRATAMA MEDAN - Simamora, Ami Rosana; Sitanggang, Develita Br; Ginting, Melitna Br (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2019)
In this study, researchers analyzed the teachers? questioning strategies in the classroom efl. This research was conducted at SMP MULIA PRATAMA MEDAN. For the class observed is class VII 4. This research is a descriptive qualitative research. The research data collection technique by observation and documentation (photos, records, and notes). At the time of the study, researchers only observed one class for 90 minutes. From the observations of the study, researchers have found what types of questions are used by the teacher in the class. The way the teacher asks when in class is teacher at the school are more likely to ask question by asking students to answer her questions, appoint students to answer the teacher?s question, give question suddenly and ask students to anwer one by one.  Based on the level of taxonomy bloom, the dominant question made by the teacher is the type of knowledge question where the question is the lowest level question and viewed from the type of question according to the breadth of the target, the question given by the teacher is more dominant on the narrow question, which only requires one answers and are closed compared to broad questions. The final conclusion of this study shows that the teacher's strategy in asking questions in the class is still lacking and not properly executed.